Outcome and survival of surgically treated acute subdural hematomas and postcraniotomy hematomas–A retrospective cohort study - Heino Iiro; Sajanti Antti; Lyne Seán B.; Frantzén Janek; Girard Romuald; Cao Ying; Ritala Joel F.; Katila Ari J.; Takala Riikka S.K.; Posti Jussi P.; Saarinen Antti J.; Hellström Santtu; et al. (Netherlands, 2025)
Background
The morbidity and mortality of acute subdural hematoma (aSDH) remains high. Several factors have been reported to affect the outcome and survival of these patients. In this study, we explored factors potentially associated with the outcome and survival of surgically treated acute subdural hematoma (aSDH), including postcraniotomy hematomas (PCHs).
Methods
This retrospective cohort study was conducted in a single tertiary university hospital between 2008 and 2012 and all aSDH patients that underwent surgical intervention were included. A total of 132 cases were identified for collection of demographics, clinical, laboratory, and imaging data. Univariate and multivariable analyses were performed to assess factors associated with three-month Glasgow Outcome Scale (GOS) and survival at one- and five-year.
Results
In this study, PCH (n = 14, 10.6%) was not associated with a worse outcome according to the 3- month GOS (p = 0.37) or one (p = 0.34) and five-year (p = 0.37) survival. The multivariable analysis showed that the volume of initial hematoma (p = 0.009) and Abbreviated Injury Scale score (p = 0.016) were independent predictors of the three-month GOS. Glasgow Coma Scale (GCS) score (p < 0.001 and p = 0.037) and age (p = 0.048 and p = 0.003) were predictors for one and five-year survival, while use of antiplatelet drug (p = 0.030), neuroworsening (p = 0.005) and smoking (p = 0.026) were significant factors impacting one year survival. In addition, blood alcohol level on admission was a predictor for five-year survival (p = 0.025).
Conclusions
These elucidations underscore that, although PCHs are pertinent, a comprehensive appreciation of multifarious variables is indispensable in aSDH prognosis. These findings are observational, not causal. Expanded research endeavors are advocated to corroborate these insights.